Свадебный подарок: роман / Салли Карлин - Карлин Салли (Любовный роман, 2002)
Экземпляры: ф.7 (2003) / Инвентарный номер: 45423 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: К 23 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44